The Effect of Individual-based and Group-based Exercise on Loneliness in the Elderly: A Quasi-Experimental Study - Azadhosseini, Meysam; Zandi, Mitra; Nasiri, Malihe; Goodarzi, Elnaz; Estebsari, Fatemeh; Latifi, Marzieh (Advances in Nursing & Midwifery, 2024)
Introduction: The impact of individual versus group-based physical activities on psychological well-being, particularly loneliness in the elderly, remains uncertain. We aimed to compare the effect of group and individual exercise on loneliness in the elderly. Methods: The present study was a quasi-experimental study with pre-test and post-test design that investigated the effect of exercise on loneliness, involving 110 elderly in Alborz province, Iran in 2021. Participants were randomly divided into three study groups (control, individual exercise and group exercise). The UCLA Loneliness Scale was used to assess the level of loneliness sensing before, immediately and one month after exercises schedule. Results: The results of intergroup comparison showed no significant difference across the three groups in the feeling of loneliness in the elderly before the interventions. Although no difference was found between individual-based and group-based exercise groups immediately after exercise, there was a meaningful difference between the control group and the other two interventional groups. The one-month trend of the change in loneliness score in both individually exercising (p = 0.002), and group-based exercising (p = 0.008) was shown to be significant. Conclusions: Since this research demonstrates that both individual and group exercise activities can alleviate feelings of isolation in elderly populations, government officials should prioritize including group fitness classes in their health initiatives targeting senior citizens.